2016
DOI: 10.1108/ijqrm-05-2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Service quality at the London 2012 games – a paralympics athletes survey

Abstract: Purpose – The purpose of this paper is to report on aspects of service quality at the London 2012 Paralympic Games, from a rather unusual perspective, the athletes. To date there has been little evidence captured about athlete’s satisfaction at sporting events, and specifically about their perceptions of the service quality provided. Design/methodology/approach – Unique “full” access to the London 2012 Paralympics allowed to the collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
(55 reference statements)
0
14
0
1
Order By: Relevance
“…However, the study does not include any more specific management implication regarding athletes in comparison to other stakeholders, such as fans or organisers. In contrast, Bamford and Dehe (2016) used the London 2012 Paralympic Game to investigate the specific service requirements of disabled athletes during the sports events. With a different focus in their works, Roy and Forest (2018) and Huyghe et al (2018) combined athlete management with the analysis of sleeping patterns.…”
Section: Athletes Logistics Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study does not include any more specific management implication regarding athletes in comparison to other stakeholders, such as fans or organisers. In contrast, Bamford and Dehe (2016) used the London 2012 Paralympic Game to investigate the specific service requirements of disabled athletes during the sports events. With a different focus in their works, Roy and Forest (2018) and Huyghe et al (2018) combined athlete management with the analysis of sleeping patterns.…”
Section: Athletes Logistics Managementmentioning
confidence: 99%
“…. (2018),Roy & Forest (2018),Bamford & Dehe(2016),Kauppi et al (2013),Bovy (2009),Wright (2009),Minis at al. (2006a),Minis et al (2006b) …”
mentioning
confidence: 99%
“…These dimensions are primary professional, primary-consumer, primary-peripheral, primary-facilitating goods, and secondary goods and services (Chelladurai & Chang, 2000). Following this line of authors who elaborate new research to generate scales that can be adapted to different types of services, researchers find contributions dedicated to the perception of perceived quality in fitness centers (Bamford, & Dehe, 2016) Among the researchers who supported the relationship between quality and satisfaction with the intentions and behaviour are Cronin, Brady, and Hult (2000), who investigated this relationship in six different industrial markets: a) sports fans, b) participants in sports activities, c) entertainment d) health institutes, e) long distance transports and f) fast food chains. The study explored suitability as a whole, as well as individually for each type of industrial market, through and the results showed a significant correlation between quality and satisfaction on behavioural intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of customer orientation as regards quality management practices in an uncertain environment is surprising, particularly as customer satisfaction is often seen as important to the success of sporting events (Bamford & Dehe, 2016;Kelley & Turley, 2001).…”
Section: Discussionmentioning
confidence: 99%